2015
DOI: 10.1007/s00253-015-6436-1
|View full text |Cite|
|
Sign up to set email alerts
|

Deciphering the role of coumarin as a novel quorum sensing inhibitor suppressing virulence phenotypes in bacterial pathogens

Abstract: The rapid unchecked rise in antibiotic resistance over the last few decades has led to an increased focus on the need for alternative therapeutic strategies for the treatment and clinical management of microbial infections. In particular, small molecules that can suppress microbial virulence systems independent of any impact on growth are receiving increased attention. Quorum sensing (QS) is a cell-to-cell signalling communication system that controls the virulence behaviour of a broad spectrum of bacterial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 76 publications
2
61
0
Order By: Relevance
“…In this study, mellein showed no antivirulence or anti-biofilm capacities. Recently, coumarin was reported to possess antivirulence and anti-biofilm capacities against P. aeruginosa (Gutiérrez-Barranquero et al, 2015). Citreoisocoumarin, one coumarin analog, showed no antivirulence or anti-biofilm capacities in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mellein showed no antivirulence or anti-biofilm capacities. Recently, coumarin was reported to possess antivirulence and anti-biofilm capacities against P. aeruginosa (Gutiérrez-Barranquero et al, 2015). Citreoisocoumarin, one coumarin analog, showed no antivirulence or anti-biofilm capacities in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Briefly, 50 μL of cell-free supernatant of FSE-treated and FSE-untreated P. aeruginosa was separately added in LB solid medium containing 5% skim milk have holes and incubated at 30°C for 18 h. The circle of casein hydrolysis was detected.…”
Section: Methodsmentioning
confidence: 99%
“…As phenol and catechol are key structural components of EA ( Figures 1 , 2 ) and other phenolic compounds have shown anti-biofilm and anti-quorum sensing activity (Cowan, 1999; Brielmann, 2010; Gutierrez-Barranquero et al, 2015; Onsare and Arora, 2015; Zhou et al, 2015; Tsou et al, 2016), they were chosen as targets to determine the structural elements of the EA core required for bioactivity. Phenol and catechol containing compounds are widely observed in plant natural products (Cowan, 1999; Brielmann, 2010), suggesting that they may occur within R. ulmifolius .…”
Section: Discussionmentioning
confidence: 99%